2017
DOI: 10.1038/onc.2017.64
|View full text |Cite
|
Sign up to set email alerts
|

Skp2 deficiency restricts the progression and stem cell features of castration-resistant prostate cancer by destabilizing Twist

Abstract: Castration-resistant prostate cancer (CRPC) remains a major clinical challenge due to the lack of effective targeted therapy for its treatment. The mechanism underlying how CRPC gains resistance towards hormone depletion and other forms of chemotherapy is poorly understood. Research on understanding the factors that drive these processes is desperately needed to generate new therapies to cure the disease. Here, we discovered a fundamental role of S-phase protein kinase 2 (Skp2) in the formation and progression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
56
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(59 citation statements)
references
References 52 publications
3
56
0
Order By: Relevance
“…On the other hand, Skp2 could combine with Myc, Miz1 and p300 to form a transcriptional complex mediating the transcription of RhoA to participate in the invasion and metastasis of tumors [36] . Furthermore, SKP2 has also been proven to enhance tumor invasion ability by promoting epithelial-mesenchymal transition (EMT) process and matrix metalloproteinase (MMP) expression [37,38] . Based on these encouraging results, Zhang et al found knockdown of Skp2 could result in RhoA and MMP-9 inhibition, thereby signi cantly reducing tumor cell invasion and lung metastasis in an orthotopic mouse model of osteosarcoma [39] .…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Skp2 could combine with Myc, Miz1 and p300 to form a transcriptional complex mediating the transcription of RhoA to participate in the invasion and metastasis of tumors [36] . Furthermore, SKP2 has also been proven to enhance tumor invasion ability by promoting epithelial-mesenchymal transition (EMT) process and matrix metalloproteinase (MMP) expression [37,38] . Based on these encouraging results, Zhang et al found knockdown of Skp2 could result in RhoA and MMP-9 inhibition, thereby signi cantly reducing tumor cell invasion and lung metastasis in an orthotopic mouse model of osteosarcoma [39] .…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesized that the doses of gemcitabine are too low to kill all GR cells, or that a small number of cells probably survive by regulating other resistance pathways (Supplementary Figure S15). However, not all the EMT-related chemoresistance is mediated by ZEB1, as reported that paclitaxel resistance in many cancer cells are conferred by overexpression of Twist [38,39]. It seems that chemoresistance in different cancer cells or induced by different chemotherapeutic drugs may depend on different mesenchymal proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Highly expressed Skp2 can serve as a poor prognosis marker in non‐small cell lung cancer . The progression of castration‐resistant prostate cancer is modulated by Skp2 via destabilizing Twist . Lung cancer cells become sensitive to drugs for Skp2 inhibition .…”
Section: Discussionmentioning
confidence: 99%
“…Overexpressed Skp2 is able to depress the radiation‐induced bystander effects in esophageal carcinoma . Skp2 destabilizes Twist to regulate castration‐resistant prostate cancer progression . Skp2 is stabilized by mammalian target of rapamycin complex 1 (mTORC1)‐mediated phosphorylation in augmentation of gastric cancer .…”
Section: Introductionmentioning
confidence: 99%